HUBUNGAN STRES KERJA PERAWAT DENGAN KEPATUHAN PERAWAT DALAM PELAKSANAAN SURGICAL SAFETY CHECKLIST (SSC) - Agustinna Laili Rachmawati; Tutik Herawati; Maria Dyah Ciptaningtyas (Poltekkes Kemenkes Malang, 2019)
Work stress negatively impacts if one s ability to deal with stress is low. Excessive stress leads to a decrease in performance. One of the performance of nurse surgical room is the implementation of SSC. The purpose of this study is to determine the relationship of nurses work stress with nurse obedience in the implementation of SSC in the surgery room Mardi Waluyo Blitar Hospital. This research uses correlational research design with cross sectional approach. The population is all nurses in the surgery room of RSUD Mardi Waluyo Blitar number of 23 people, by using purposive sampling technique got sample as much 16 person (circular nurse). The instrument used is a questionnaire about work stress and an observation sheet about SSC. The result of univariate analysis was found that most of surgical nurses of Mardi Waluyo Blitar Hospital experienced mild stress, 13 people (81 percent). Then, most of surgical nurses Mardi Waluyo Blitar RSUD did not obey the whole point in the SSC that is 10 people (63 percent). The result of bivariate analysis using Spearman correlation test obtained p is 0,039, it means there is relation between nurses work stress with nurse compliance in SSC implementation in RSUD Mardi Waluyo Blitar surgery room. The recommendation of the results of this study is that you can find factors that may affect patients in the surgical safety checklist (SSC) aside from occupational stress factors.